Antibiotics Separation with MXene Membranes Based on Regularly Stacked High‐Aspect‐Ratio Nanosheets. Issue 24 (17th April 2020) - Li, Zhong‐Kun; Wei, Yanying; Gao, Xue; Ding, Li; Lu, Zong; Deng, Junjie; Yang, Xianfeng; Caro, Jürgen; Wang, Haihui
Abstract: The uncontrolled release of antibiotics and pharmaceuticals into the environment is a worldwide increasing problem. Thus, highly efficient treatment technologies for wastewater are urgently needed. In this work, seven kinds of typical antibiotics (including water and alcohol soluble ones) are successfully separated from the corresponding aqueous and ethanolic solutions using highly regular laminated membranes. Our membranes are assembled with 2–4 μm titanium carbide nanosheets. The solvent permeance through such titanium carbide membrane is one order of magnitude higher than that through most polymeric nanofiltration membranes with similar antibiotics rejection. This high flux is due to the regular two‐dimensional (2D) structure resulting from the large aspect ratio of titanium carbide nanosheets. Moreover, the electrostatic interaction between the surface terminations and the antibiotics also affects the rejection and enhances the antifouling property. Such 2D titanium carbide membranes further broaden the application scope of laminated materials for separation and purification of high value added drugs in academia and industry. Abstract : A laminated membrane with a highly regular 2D structure assembled by MXene nanosheets with a high lateral ratio shows a one order of magnitude higher solvent permeance than that through most polymeric nanofiltration membranes with similar antibiotic rejection.